1982
DOI: 10.1093/ajcn/36.5.986
|View full text |Cite
|
Sign up to set email alerts
|

Calcium nutrition and bone health in the elderly

Abstract: The average elderly person is in negative calcium balance and accordingly is losing bone mass. While factors such as decreased mechanical loading of the skeleton undoubtedly figure in this age-related loss, a growing body of evidence suggests that inadequate calcium intake may contribute to this loss. On any given day men and women in the US 65 yr or older ingest about 600 and 480 mg calcium, respectively. Calcium intake in the elderly is less than in the young, and reduced absorption efficiency further lowers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
82
1
4

Year Published

1984
1984
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(89 citation statements)
references
References 117 publications
2
82
1
4
Order By: Relevance
“…There is some speculation that age-related renal impairment decreases the renal hydroxylation of vitamin D, thereby decreasing the amount of active vitamin D available for Ca absorption (Heaney et al 1982). Many institutionalized and free-living elderly (up to 50 % in some studies) have inadequate vitamin D intake, and the possible causes for this include sunlight deprivation, decreased intake of diary products, lactose intolerance and malabsorption of fat-soluble vitamins (Hoffman, 1993).…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some speculation that age-related renal impairment decreases the renal hydroxylation of vitamin D, thereby decreasing the amount of active vitamin D available for Ca absorption (Heaney et al 1982). Many institutionalized and free-living elderly (up to 50 % in some studies) have inadequate vitamin D intake, and the possible causes for this include sunlight deprivation, decreased intake of diary products, lactose intolerance and malabsorption of fat-soluble vitamins (Hoffman, 1993).…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
“…Ca alone without oestrogens cannot fully ameliorate post-menopausal bone loss, but Ca supplementation of 1000 mg daily with exercise does slow bone loss (Prince et al 1991). Although Ca supplementation may be necessary for certain groups of elderly people, it may be harmful in patients with a history of Ca stones, primary hyperparathyroidism, sarcoidosis or renal hypercalcuria (Heaney et al 1982). Recently, a randomized doubleblind placebo-controlled trial of the effects of 3 years of dietary supplementation with Ca and vitamin D in 176 men and 213 women over 65 years of age reported that dietary Alzheimer's disease delayed by 50 % the combined end point of death, admission to an institution, inability to perform the activities of daily living, or severe dementia (Sano et al 1997) In another trial eighty-eight healthy people aged 65 years or older were randomized to receive a-tocopherol (mg/d; 40, 130 or 430) or placebo.…”
Section: Calcium and Vitamin Dmentioning
confidence: 99%
“…Consoante Hill et al 5 , a gordura proveniente da dieta é considerada determinante primária de obesidade, sendo esta mais prevalente em mulheres a partir do climatério 6 . Outros estudos revelam deficiência de nutrientes, como as vitaminas A e C 4,7 , o cál-cio 2,[8][9][10] e o ferro 4 .…”
Section: Introductionunclassified
“…During ageing process, it has been reported that adequate calcium intake maintain the bone growth and avert bone loss. There have been growing evidence reporting that inadequate calcium intake may put in calcium loss because of decreased mechanical loading of the skeleton because of ageing [3].…”
Section: Introductionmentioning
confidence: 99%